Abnormal late postprandial glucagon response in type 1 diabetes is a function of differences in stimulated C-peptide concentrations - Zhang, Lingyu; Qin, Yao; Huang, Yiting; Hu, Qizhen; Wu, Qian; Wang, Xing; Zhang, Mei (Frontiers in Endocrinology, 2024)
The functional changes in alpha cells in patients with type 1 diabetes (T1D) with different residual beta cell functions remain poorly elucidated. The study aimed to investigate the relationship between glucagon secretion and C-peptide levels and to explore the relationship between glucagon response and glucose increment in respond to a secretagogue in a steamed bread meal tolerance test (BMTT) in T1D.The study enrolled 43 adult patients with T1D and 24 healthy control subjects. Patients with T1D who underwent BMTT were divided into two groups based on peak C-peptide levels: C peptide low (CPL; C-peptide < 200 pmol/L; n=14) and high (CPH; C peptide ≥ 200 pmol/L; n=29). Plasma glucose, C-peptide, glucagon levels at 0, 30, 60, 120, and 180 min were measured. The glucagon response to the BMTT was defined by areas under the curve (AUC) as early (AUC0-30), late (AUC30-180), or total (AUC0-180) glucagon.Results: Compared to healthy individuals, fasting plasma glucagon was lower and postprandial plasma glucagon level was increased in patients with T1D. Glucagon levels after BMTT between the CPL and CPH group showed significant group by time interaction. Peak glucagon and glucagon at 60-180 min, total and late glucagon response were higher in CPL than CPH group, while fasting glucagon and early glucagon response adjusted for glucose were comparable between CPL and CPH group. The higher late glucagon response and late glucagon response adjusted for glucose were associated with lower peak C-peptide in T1D. The higher late glucagon response and lower peak C-peptide were associated with the higher value of △glucose at 180 min.Conclusions: Stimulated C-peptide levels affect the paradoxical increase in postprandial glucagon secretion in patients with T1D, especially late glucagon response. The exaggerated postprandial glucagon secretion further stimulates the elevation of postprandial glucose in patients with T1D.